Wat verbeeldt de christelijke gemeente zich als ze zegt dat God haar aanspreekt? - Dulk, Maarten Den (HTS teologiese studies, 2002)
In what manner does the Christian congregation imagine God to be addressing her?In the reading and preaching of Scriptures people speak to one another about God. These actions are surrounded by words, gestures and rituals directed to God. However, the congregation also claims that God is addressing her. Hence, this article poses the question: In what manner does the congregation imagine God to be addressing her? Which images and parables are used for this purpose? In dealing with this question the article focuses on the words in Numbers 7:89 relating how Moses heard a voice coming from the space between the two cherubim standing on the atonement cover on the ark of the Testimony. This verse offers an indication of how believers can presume God to be speaking in liturgical space.